Combined effects of levetiracetam and sodium valproate on paediatric patients with epilepsy: a systematic review and meta-analysis. (February 2022) - Zhu, Yifei; Yang, Junlan; Zhu, Xinjian
Highlights: Sodium valproate combined with levetiracetam significantly improves the therapeutic effect in children with epilepsy Sodium valproate combined with levetiracetam reduces adverse drug reaction in children with epilepsy Sodium valproate combined with levetiracetam are recommended in the therapy of paediatric patients with epilepsy Abstract: Objective: To estimate the safety and efficacy of sodium valproate combined with levetiracetam in paediatric patients with epilepsy based on randomized controlled trials (RCTs). Methods: The Cochrane Library, PubMed, Web of Science, Chinese Journal Full-Text Database (CNKI), WANGFANG DATA and Sino Med were searched between January 1946 and May 2021. The included literature was randomized controlled clinical trials focusing on sodium valproate combined with levetiracetam in paediatric patients with epilepsy. Two evaluators separately collected the data based on the retrieval strategy, filtered the literature in accordance with the inclusion and exclusion criteria, and summarized the literature that satisfied the criteria. The statistical programme used for the meta-analysis was Stata V14.0. Results: Of 577 original titles screened, data were extracted from 7 studies (617 participants). Compared with sodium valproate alone or sodium valproate combined with topiramate, the application of sodium valproate combined with levetiracetam in the treatment of paediatric epilepsy significantly improved the overall therapeutic effect (RR=1.24, 95% CI: 1.16 to 1.33, p =0.927). The observation group significantly reduced the occurrence of adverse drug reactions (ADRs) (RR=0.54, 95% CI: 0.37 to 0.79, p =0.602). Egger's regression test of the overall therapeutic effect showed no potential publication bias ( p =0.122). Conclusion: Based on this meta-analysis, compared with sodium valproate alone or sodium valproate with topiramate, the application of sodium valproate combined with levetiracetam in the treatment of paediatric epilepsy can significantly improve the overall therapeutic effect and simultaneously reduce the occurrence of ADR. Therefore, we recommend sodium valproate combined with levetiracetam for the therapy of paediatric patients with epilepsy.